Fig. 7 in A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Amano, Kazutaka; Bitner, Maria Aleksandra; Hagström, Jonas; Kiel, Steffen; Klompmaker, Adiël A.; Mörs, Thomas; Robins, Cristina M.; Kaim, Andrzej (Zenodo, 2019)
Fig. 7. Non-chemosymbiotic protobranch bivalves from the upper Paleocene, Basilika Formation, Fossildalen (A–E, G, I–K) and Zachariassendalen (F, H), Spitsbergen, Svalbard. A.?Nucula sp., ZPAL V.48/10, internal mold of right valve. B.?Malletia sp., ZPAL V.48/11, right valve. C, D. Neilonella sp. C. ZPAL V.48/12, left valve sculptured by fine commarginal ribs. D. ZPAL V.48/13, partial shell, right valve (D1), dorsal view of both valves (D2). E–K. Yoldiella spitsbergensis Amano sp. nov. E. Holotype, ZPAL V.48/17, internal mold, right valve (E1), hinge part (E2). F. Paratype, NRM-PZ Mo 186241, silicified shell, hinge part (F1), outer surface (F2). G. Paratype, ZPAL V.48/18, internal mold, right valve (G1), hinge part (G2). H. Paratype, NRM-PZ Mo 186242, silicified shell, right valve. I. ZPAL V.48/19, internal mold, left valve. J. ZPAL V.48/20, partial shell, left valve. K. ZPAL V.48/21, partial shell, partly preserved outer surface, left valve. Published as part of Hryniewicz, Krzysztof, Amano, Kazutaka, Bitner, Maria Aleksandra, Hagström, Jonas, Kiel, Steffen, Klompmaker, Adiël A., Mörs, Thomas, Robins, Cristina M. & Kaim, Andrzej, 2019, A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard, pp. 101-141 in Acta Palaeontologica Polonica 64 (1) on page 111, DOI:10.4202/app.00554.2018, http://zenodo.org/record/10980900